Advances in theta-burst transcranial magnetic stimulation for auditory comprehension deficits in post-stroke aphasia - Jing, Yuling; Duan, Haoyang; Yang, Wendong; Zhang, Hong; Dong, Lianxi; Li, Zhenlan (Frontiers in Neurology, 2025)
Aphasia is a language network disorder caused by organic brain lesions, which severely affects patients' daily communication and interaction. The therapeutic effect of conventional rehabilitation training alone is limited. Currently, Theta Burst Stimulation (TBS) is a novel therapeutic modality of repetitive Transcranial Magnetic Stimulation (rTMS) and is a commonly used patterned rTMS. It appears in the form of burst waves and mimics the natural firing pattern of hippocampal neurons under Theta rhythm. Based on rTMS, TBS embeds a pattern in which three 50 Hz pulse bursts are inserted into a 5 Hz pulse train. This stimulation pattern can induce cortical plasticity in a shorter period of time and is gradually being applied in the treatment of aphasia. Auditory comprehension, as the initial component of language input, involves the reception and storage of linguistic signals, as well as the analysis and integration of lexical semantics. The recovery of this ability plays a prerequisite role in the functional improvement of patients with post-stroke aphasia (PSA). In recent years, research on aphasia has mainly focused on speaking, reading, and writing abilities, with relatively less attention paid to auditory comprehension. Therefore, this article reviews the research progress related to the use of TBS in treating auditory comprehension in aphasia, aiming to provide new ideas and references for the clinical selection of TBS stimulation protocols.